To Be a Sportsman? Sport Participation Is Associated With Optimal Academic Achievement in a Nationally Representative Sample of High School Students - Chen, Sitong; Li, Xiaoyun; Yan, Jin; Ren, Zhanbing (Frontiers in Public Health, 2021)
In the present study, the relationship between academic achievements and participation in a sports team in adolescents has been identified using nationally representative data. The study sample was created by referring to the U.S. Youth Risk Behavior Surveillance 2019 cycle, of which were eligible samples in the current study. A self-reported questionnaire was used to assess the participation in sports (0, one, two, three or more teams) and academic performance (mostly A, mostly B, mostly C, mostly E, mostly F). Controlling variables included sex, age, grade, race/ethnicity, adherence to physical activity, sleep guidelines and screen time, respectively. A binary regression model with an odds ratio (OR) at 95%CI confidence interval was performed to examine the association between sports team participation (0 teams as reference) and academic performance (combination of mostly C, E, F as reference). Results showed that compared with study participants with no participation in any sports teams, participating in one, two, three or more teams were more likely to self report better academic performance (1 teams: odds ratio [OR] = 1.48; two teams: OR = 2.34; three or more = 2.72), demonstrating a dose despondent association. This dose-dependent association varied slightly across sexes and grades. In conclusion, consistent with previous studies, the current study confirmed the positive roles of sport participation on academic outcomes in adolescents. Sex- and grade-specific strategies should be considered for academic-relevant promotion.